Towards the Effectiveness of Utilizing ICT in Enhancing Language Learning Process: A Pilot Study - Hafizoah, Kassim; Haslinda, Hashim; Noor Raha, Mohd Radzuan (2005)
In the educational arena, technology in general and the Information & Communication Technology (ICT) in particular have become one of the significant tools in enhancing language learning process. Furthermore, the support to realize Vision 2020 has inspired many language practitioners to integrate ICT into their language classes. However, many questions have arisen demanding for answers: Can ICT really enhance language learning process? How effective can it be? Can ICT change students’ attitudes towards language learning? And most importantly, what are the technological resources and tools that can be effectively utilized? In language education, these questions have provided a new dynamic field of research. On this basis, this paper will move towards uncovering the effectiveness of utilizing ICT in enhancing language learning process. This move will go beyond the conventional 'board and chalk' approach; thus, it is vital that relevant theories or models of learning are provided. ICT resources will also be identified in order to demonstrate the significance of ICT in maximizing student-centered learning (SCL) approach. Findings of research are gathered from questionnaire and interviews which are conducted in University College of Engineering & Technology Malaysia (KUKTEM), Pahang, Malaysia.